Optimized Preparation of Nanosized Hollow SSZ-13 Molecular Sieves with Ultrasonic Assistance - Liang Zhou (Nanomaterials, 2020)
Because of its unique eight-membered ring pore structure and the arrangement of cations in its structure, the SSZ-13 molecular sieve has a higher affinity for CO2 than other gases, meaning it has attracted more attention than other porous materials for CO2 adsorption. However, the expensive template and long preparation time limits the industrial production of SSZ-13. In this work, a hollow structure was successfully introduced into the nanosized SSZ-13 molecular sieve with ultrasonic treatment. The effects of the amount of seed added and the ultrasonic time on the structure were investigated. When the amount of seed added was 0.5 wt.% and the ultrasonic time was 60 min, the sample showed a hollow cubic crystal with a diameter of about 50 nm. The specific surface area reached 791.50 m2/g, and the mesoporous ratio was 66.3%. The samples were tested for CO2 adsorption performance at 298 K. It was found that the hollow sample prepared in this work has higher CO2 adsorption capacity compared with the SSZ-13 zeolite prepared with conventional methods. When the adsorption pressure was 0.27 bar, the adsorption amount reached 2.53 mmol/g. The hollow SSZ-13 molecular sieve reached a CO2 adsorption capacity of 4.24 mmol/g at 1 bar.